Complications in vertebroplasty. - Areesak Chotivichit (2018)
Vertebroplasty is one of the minimally invasive surgery that benefit in pain relief from the osteoporotic or malignancy related vertebral compression fractures. However, many literatures reported both asymptomatic and serious complications. The aim of the present study was to summarize, collect data and report the complication ofvertebroplastyfrom our experience at a single institute. Three hundred and twenty five vertebroplasty procedures from 236 patients performed in our institute were retrospectively reviewed. Data of diagnosis, age at the time of procedure were collected. All complications found were reviewed in detail. Commonly performed procedures were at thoracolumbar junction (51.4%). Osteoporosis was the most common cause of fracture. The present study found 88 (27%) complications with 26 (8%) symptomatic patients. Most common complication was cement leakage, which intervertebral disc was the most common site (42.9). Spinal canal leakage was found in 14 cases (20%). Four out of 14 cases had neurological complications and need further managements. Two cases had neurologic complications from needle injury.Adjacent level collapse found in 13 patients (4%) and remote segment collapse occurred in 5 patients (1.5%). Three had progressive kyphosis required later surgical treatment. One asymptomatic cement pulmonary embolism was found in the present study. The complications of vertebroplasty were mostly asymptomatic, but serious complication such as neurologic injury could occur. Vertebroplasty could be considered a quite safe treatment for osteoporotic vertebral fracture. Meticulous technique should be executed during the procedure to avoid the leakage complication.